Illness Severity Predicts Death and Brain Injury in Asphyxiated Newborns Treated with Hypothermia - Wang, Hui; Beltempo, Marc; Rampakakis, Emmanouil; Sanon, Priscille-Nice; Barbosa Vargas, Stephanie; Maluorni, Julie; Saint-Martin, Christine; Wintermark, Pia (American Journal of Perinatology, 2018)
Objective To determine if illness severity during the first days of life predicts adverse outcome in asphyxiated newborns treated with hypothermia.Study Design We conducted a retrospective cohort study of asphyxiated newborns treated with hypothermia. Illness severity was calculated daily during the first 4 days of life using the Score for Neonatal Acute Physiology II (SNAP-II score). Adverse outcome (death and/or brain injury) was recorded. Differences in SNAP-II scores between the newborns with and without adverse outcome were assessed.Result 214 newborns were treated with hypothermia. The average SNAP-II score over the first 4 days of life was significantly worse in newborns developing adverse outcome. The average SNAP-II score was an excellent predictor of death (area under the curve [AUC]: 0.93; p < 0.001) and a fair predictor of adverse outcome (AUC: 0.73; p < 0.001). The average SNAP-II score remained a significant predictor of adverse outcome (odds ratio [95% confidence interval]: 1.08 [1.04–1.12]; p < 0.001), after adjusting for baseline characteristics, degree of initial asphyxial event, and initial severity of encephalopathy.Conclusion In asphyxiated newborns treated with hypothermia, not only the initial asphyxial event but also the illness severity during the first days of life was a significant predictor of death or brain injury.
Keywords: birth asphyxia; brain; neonatal encephalopathy; newborn; SNAP-II score